1992
DOI: 10.1007/bf01973627
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the response of Sprague-Dawley and Lewis rats to bezafibrate: The hypolipidemic effect and the induction of peroxisomal enzymes

Abstract: The effects of bezafibrate administered at 10 and 50 mg/kg/day for 7 days to male Sprague-Dawley (SD) and Lewis rats were investigated in order to determine the interrelation between the changes in serum and hepatic lipid contents and activities of selected peroxisomal, microsomal and mitochondrial enzymes in the two rat strains. In both strains, bezafibrate effectively reduced serum and hepatic lipids, increased the liver weight, induced a proliferation of peroxisomes, and selectively elevated the activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It is interesting that this hormone is a peroxisome proliferator [12,15,24,25,31]. Most peroxisome proliferators including clofibrate [9,27] and bezafibrate [13,22,23] are hypolipidemic agents, and decrease serum triglycerides and cholesterol. Some of these peroxisome proliferators were reported to be capable of metabolizing and diminishing intracellular lipid droplets [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that this hormone is a peroxisome proliferator [12,15,24,25,31]. Most peroxisome proliferators including clofibrate [9,27] and bezafibrate [13,22,23] are hypolipidemic agents, and decrease serum triglycerides and cholesterol. Some of these peroxisome proliferators were reported to be capable of metabolizing and diminishing intracellular lipid droplets [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…Despite these similarities, clofibrate elevated microsomal epoxide hydrolase activity accompanied by a decrease in glutathione transferase activity only in the Sprague-Dawley strain. Similarly, Pill et al (1992) found that LEW rats were far more susceptible to peroxisomal proliferation than Sprague-Dawley animals, as evidenced by the marked rise in hepatic total peroxisomal oxidation activities and cytochro me c oxidase activity in LEW rats. In a comparison of various strains Makowska et al (1990) demonstrated that ciprofibrate induced a ninefold increase in peroxisomal fatty acid-oxidase in Sprague-Dawley, Wistar, and F344 strains, whereas a marked 35-fold elevation was noted in Long-Evan s rats.…”
Section: Peroxisomal Proliferationmentioning
confidence: 86%
“…The impact of bezafibrate on hyperlipidemic hamsters has not yet been evaluated, and a previous dose–response study with fenofibrate suggested that the dose commonly used in mouse was efficacious in hamsters [15], [17], [18], [41]. We thus reasoned this may also be the case for bezafibrate, and selected daily dosing of 25 and 50 mg kg − 1 bezafibrate based on earlier rodent models’ studies in which 10 mg kg − 1 was the lowest effective dose for lowering serum lipids in rats [29], [42][45]. According to present results, we thus can presume that the dyslipidemia in hamsters may be more severe than that in mice or rats.…”
Section: Discussionmentioning
confidence: 99%